THE IMPORTANCE OF IMMUNOHISTOCHEMICAL LIVER EXAMINATION IN FORENSIC MEDICINE FOR CASES OF DEATH FROM SURROGATE ALCOHOL POISONING (PROBLEMS AND SOLUTIONS OF SCIENTIFIC AND INNOVATIVE RESEARCH, 2025)
Histological changes in the liver in surrogate alcohol poisoning are reflected. Characteristics of "toxic hepatitis" are given in dynamics, taking into account tissue reactions and cell cooperation. The distribution of Kupffer cells was studied, assessing their role in the course and outcome of liver damage. Sectional materials, histological and immunohistochemical research methods, clinical and additional data were used.